A multifaceted assessment of strigolactone GR24 and its derivatives: from anticancer and antidiabetic activities to antioxidant capacity and beyond - Pyrzanowska-Banasiak, Agata; Boyunegmez Tumer, Tugba; Bukowska, Bożena; Krokosz, Anita (Frontiers in Molecular Biosciences, 2023)
Background: Strigolactones are signaling molecules produced by plants, the main functions are the intracorporeal control of plant development and plant growth. GR24 strigolactone is one of the synthetic strigolactones and due to its universality and easy availability, it is a standard and model compound for research on the properties and role of strigolactones in human health. Purpose: In this research work, the impact of mainly GR24 strigolactone on the human body and the role of this strigol-type lactone in many processes that take place within the human body are reviewed. Study design: The article is a review of publications on the use of GR24 strigolactone in studies from 2010-2023. Publications were searched using PubMed, Elsevier, Frontiers, and Springer databases. The Google Scholar search engine was also used. For the review original research papers and reviews related to the presented topic were selected. Results: The promising properties of GR24 and other strigolactone analogs in anti-cancer therapy are presented. Tumor development is associated with increased angiogenesis. Strigolactones have been shown to inhibit angiogenesis, which may enhance the anticancer effect of these γ-lactones. Furthermore, it has been shown that strigolactones have anti-inflammatory and antioxidant properties. There are also a few reports which show that the strigolactone analog may have antimicrobial and antiviral activity against human pathogens. Conclusion: When all of this is considered, strigolactones are molecules whose versatile action is their undeniable advantage. The development of research on these phytohormones makes it possible to discover their new, unique properties and surprising biological activities in relation to many mammalian cells.